Impact of individualized education plans on academic success of youth with early onset schizophrenia. Issue 5 (3rd September 2018) - Ball, Annahita; Rittner, Barbara; Chen, Ya-Ling; Maguin, Eugene
ABSTRACT: Purpose : Youth with early onset schizophrenia (EOS) are eligible for an individualized education plan (IEP) in school settings, yet often have declining academic performance over time. This study examines the impact of IEP and comorbid conditions on educational outcomes for youth with EOS. Method : We used mixed models and logistic regression to answer the research questions using data from 129 youth with EOS who participated in a longitudinal study from 1998 to 2006. Results : Not all children had an IEP in all waves. Of those that did, findings demonstrated that having an IEP did not improve absenteeism or academic performance. In addition, regardless of whether they had an IEP, rates of dropping out were equal. Conclusions : Social workers should consider more individualized approaches to IEPs for youth with EOS to target the specific complexities of the disorder as well as its implications for school success.